Applying a New Theory to Alter Binge Drinking Behavior in College Students. Issue 1 (January 2017) - Sharma, Manoj; Knowlden, Adam P.; Nahar, Vinayak K.
Abstract : Binge drinking is a serious public health problem in the United States, where it is estimated that 17.6% adults binge drink. Binge drinking is highest among college students. There is need for effective binge drinking interventions. Recently a new health behavior theory has been proposed called the multitheory model of health behavior change. The purpose of this article is to describe the application of the multitheory model for changing binge drinking behavior to a behavior of responsible drinking or abstaining from alcohol. A framework for an intervention and its testing is presented.